Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1074/jbc.m109.021048
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle AMP-activated Protein Kinase Is Essential for the Metabolic Response to Exercise in Vivo

Abstract: AMP-activated protein kinase (AMPK) has been postulated as a super-metabolic regulator, thought to exert numerous effects on skeletal muscle function, metabolism, and enzymatic signaling. Despite these assertions, little is known regarding the direct role(s) of AMPK in vivo, and results obtained in vitro or in situ are conflicting. Using a chronically catheterized mouse model (carotid artery and jugular vein), we show that AMPK regulates skeletal muscle metabolism in vivo at several levels, with the result tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
151
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 127 publications
(176 citation statements)
references
References 56 publications
20
151
4
Order By: Relevance
“…These conclusions are consistent with previous studies in which AMPK␣ 2 was shown to be a necessary signal in the regulation of substrate metabolism during muscle contraction or treadmill exercise (24,25). However, our data are not consistent with some additional reports in which low AMPK␣ 2 activity did not affect muscle glucose clearance during treadmill exercise (26), glucose uptake in contracting extensor digitorum longus muscle, which is a mixed-fiber type muscle (10), or FA oxidation in isolated muscle during muscle contraction or following treadmill exercise (4,10,25,29,30).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…These conclusions are consistent with previous studies in which AMPK␣ 2 was shown to be a necessary signal in the regulation of substrate metabolism during muscle contraction or treadmill exercise (24,25). However, our data are not consistent with some additional reports in which low AMPK␣ 2 activity did not affect muscle glucose clearance during treadmill exercise (26), glucose uptake in contracting extensor digitorum longus muscle, which is a mixed-fiber type muscle (10), or FA oxidation in isolated muscle during muscle contraction or following treadmill exercise (4,10,25,29,30).…”
Section: Discussionsupporting
confidence: 82%
“…Consistent with previous data in the same mouse model (31,32), DN mice had lower resting muscle glycogen content and did not utilize glycogen to the same extent as the WT mice during muscle contraction. However, this is not consistent with recent reports suggesting similar or higher rates of glycogen utilization during treadmill exercise in muscle of mice with low AMPK␣ 2 activity (24,26). Given that glycogen use and mean glucose uptake and FA oxidation were lower in the DN mice during muscle contraction, alternate fuel sources must have been used to maintain force production.…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations